Proposal for the conversion of Eucalyptus urograndis into bioethanol via acid hydrolysis, using the concepts of biorefineries - Camargo, Sâmique Kyene De Carvalho Araújo [UNESP]; Ventorim, Gustavo [UNESP]; Camargo, Bruno Silva [UNESP]; Salvador, Rodrigo; De Carvalho Araújo, Cristiane Karyn; De Carvalho Araújo, Camilla Kawane Ceciliano [UNESP]; Henrique Antunes Vieira, Fábio (My University, 2022)
The production of bioethanol from materials of renewable origin is an important matter for a more sustainable economic development, and at the same time it challenges researchers to seek more efficient technologies that can make it viable. Wood is a profitable and advantageous option, with special emphasis on eucalyptus, whose cultivation has high turnover in Brazil, where land is available for this purpose. Therefore, the goal of this research was to optimize the hydrolysis stage using acid instead of enzymes for the conversion of chips of Eucalyptus urograndis into bioethanol, with additional co-production of furfural and commercial lignin, in order to make the process more advantageous. To obtain bioethanol, a pre-treatment adapted from autohydrolysis was performed to remove the hemicelluloses, followed by soda pulping to remove the lignin and, finally, the acid hydrolysis of the β-(1→4) glycosidic bonds between the C1-C4 cellulose carbons releasing β-D-glucose monomers to be fermented into bioethanol. In the acid hydrolysis step, sulfuric acid of concentration 1127 gL-1 was used. After the experimental analyses performed, it could be observed that in acid hydrolysis, treatments using 70 mL and 80 mL of sulfuric acid did not differ statistically in relation to glucose production. However, by increasing the volume of acid to 90 mL, there was an increase in the production of fermentable sugars into bioethanol, 63.7 %, which began decreasing when adding acid above 93 mL, because the excess of acid also caused the degradation of sugars into 5-hydroxymethylfurfural (HMF); and in the treatment of 100 mL there was a higher production of HMF. The production of bioethanol proved to be competitive after the fermentation of the sample from the 90 mL treatment with a production of 103.7 L of bioethanol/ton of wood, in addition to being beneficial to the process as a whole with the co-production of furfural, 28.8 kg of furfural ton-1 of wood, and commercial lignin, 428.3 kg of lignin per ton of wood, precursors to various chemicals such as resins, coatings and inks.
Keywords: co-production of furfural; co-production of sulfur-free lignin; second generation bioethanol; soda pulping; wood pulp